INDONESIAN PASSPORT AS A REJECTION OF THE MEASUREMENT OF STATE SOVEREIGNTY - Putranto Argi Noviantoko (Jurnal Ilmiah Kajian Keimigrasian, 2019)
A passport is a travel document for every citizen to be able to travel abroad. However, a passport is not just a travel document, but can be an indicator of a country's civilization system whether it is progressing or being or even retreating. Visa politics as an analytical concept to open up a situation in a certain country. This paper wants to explain Indonesia's position in various aspects of contemporary nationality and statehood in order to become an evaluation tool for state development through the power of passports. The passport turns out to be a benchmark for a country's civilization in various aspects such as the domestic economy, domestic security, geo-geography, education and health based on international relations. The power of diplomacy is not sufficient for giving international trust to a country, but the aspects mentioned above can be used as a benchmark for a country's civilization to be trusted in the international community.